–6p + 7 = 3(2p – 3) – 4(–10 + 4p)

1 answer

-6p + 7 = 3(2p - 3) - 4(-10 + 4p)

First, distribute 3 to both terms inside the bracket:
-6p + 7 = 6p - 9 - 4(-10 + 4p)

Next, distribute -4 to the terms inside the bracket:
-6p + 7 = 6p - 9 - (-40 + 16p)

When removing the double negative, we obtain:
-6p + 7 = 6p - 9 + 40 - 16p

Combine like terms:
-6p + 7 = -10p + 31

Now, move all terms to one side of the equation:
-6p + 10p = 31 - 7

Combine like terms:
4p = 24

Finally, solve for p by dividing both sides by 4:
p = 6